2016
DOI: 10.1159/000444714
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Detection and Sizing of the <b><i>HTT</i></b> CAG Repeat Expansion in Huntington Disease Using an Improved Triplet-Primed PCR Assay

Abstract: Background: Accurate determination of the CAG repeat number is crucial for diagnostic and predictive testing for Huntington disease (HD). Current PCR-based assays can accurately size up to ∼110 HTT CAG repeats. Objective: To develop an improved assay capable of detecting larger CAG repeat expansions. Methods: A triplet-primed PCR (TP-PCR) assay was optimized and validated on 14 HD reference DNAs, including a sample carrying a large expansion of ∼180 CAG repeats. Results: All 14 HD reference samples showed 100%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…In this study, we have coupled TP-PCR with MCA to develop an improved, inexpensive yet accurate one-step assay to rapidly rule in/out HD. Comparisons with the repeat-flanking PCR MCA assay showed that the TP-PCR MCA assay has a better detection sensitivity for expanded alleles, with accurate sizing of the expanded allele of up to at least ~180 CAG repeats directly from the TP-PCR MCA product, similar to what has been achieved with TP-PCR and CE directly from genomic DNA [19]. We also showed that samples carrying only normal alleles produced normalized melt curves and derivative melt peaks with reproducibly lower T m s compared to samples carrying an expanded allele.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we have coupled TP-PCR with MCA to develop an improved, inexpensive yet accurate one-step assay to rapidly rule in/out HD. Comparisons with the repeat-flanking PCR MCA assay showed that the TP-PCR MCA assay has a better detection sensitivity for expanded alleles, with accurate sizing of the expanded allele of up to at least ~180 CAG repeats directly from the TP-PCR MCA product, similar to what has been achieved with TP-PCR and CE directly from genomic DNA [19]. We also showed that samples carrying only normal alleles produced normalized melt curves and derivative melt peaks with reproducibly lower T m s compared to samples carrying an expanded allele.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of the TP-PCR primers have been described elsewhere [19]. Other TP-PCR MCA assays were performed on a LightCycler ® 480 Real-Time PCR System (Roche Diagnostics, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to standard PCR, the triplet primed PCR (TP-PCR) method, which was first described by Warner et al . 22 , consistently detects the presence of the expanded allele regardless of its repeat length 2730 . TP-PCR utilizes three primers – a fluorescently labeled gene-specific 5′ flanking primer, a tailed triplet-primed (TP) primer, and a tail primer.…”
Section: Introductionmentioning
confidence: 95%
“…We describe a versatile strategy for HD PGT-M involving the use of TP-PCR for robust detection of the HTT CAG repeat expansion 30 , in combination with multiplex-PCR analysis of 13 closely linked microsatellite markers to establish disease haplotype phase 32 . We also report the first clinical application of this strategy for IVF PGT-M of HD in an at-risk couple for which family members of the affected spouse were unavailable for development of a standalone linkage-based PGT-M.…”
Section: Introductionmentioning
confidence: 99%